Constraints of History Teachers in the 2013 Curriculum Using a Scientific Approach at SMK Negeri 7 Semarang - Burhanudin, Muhammad; Sodiq, Ibnu (Universitas Negeri Semarang, 2016)
The purpose of this research is to know the implementation of learning history in curriculum 2013 using a scientific approach, to find out what constraints experienced by history teachers in the 2013 curriculum using a scientific approach, and to find out how history teachers overcome obstacles in the 2013 curriculum using a scientific approach This research uses data collection method in the form of observation, interview, and document study. Observation focuses on the implementation of learning using a scientific approach. Document study in this research is the syllabus, RPP, the result of student tasks, and mastery in authentic assessment—technique examination of data validity using triangulation of source and triangulation technique. Data analysis techniques use hypothesis analysis, which is a proposition. The results of this study indicate that in implementing the scientific approach to history, teachers in SMK Negeri 7 Semarang experienced quite complex constraints. The implementation of history learning in the 2013 curriculum uses a scientific approach with 5 M (observing, asking, reasoning, trying, and networking). The obstacles experienced by history teachers in SMK Negeri 7 Semarang are the constraints of time allocation, authentic assessment constraints, and teacher creativity constraints. The solution made by the history teacher at SMK Negeri 7 Semarang is concerned with historical learning materials by reducing aspects of authentic assessment and using varied learning methods so that learning is not monotonous.